Culture in Manchester : Institutions and urban change since 1850 - Savage, Michael, 1959-; Wolff, Janet (Book collections on Project MUSE., 2013)
This book brings together studies of cultural institutions in Manchester from 1850 to the present day, giving an unprecedented account of the city's cultural evolution.